(3eNJGQ GdCZGfj aj GdCNHGQ hGdJgGfjs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfbGd GdeUfa QMeg Gddg JYGdi(B: (3CbOe gfG McGjI hLOJgG aj BNQ eNJUQ ef gPG GdcJGH, GNJUQg GdQTjO GHhGdMSjf CMeO Hf GdQTjOj GdRHjQ s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO ajgG(B: (3hcGf GdCbjTQ dG jSCd CMOkG CcKQ ef NeSI OQGge aCJi jhekG ef GdCjGe HjJ Mfjf GdNqeGQ GdPj cGf jCJjg ade jUGOag, aLYd jfJXQg aONdJ s
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B108 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B46s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B17 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs